(untitled) (The Voz a Vos Bulletin, 2023)
This paper is part of the memory of the systematization of the play Villaovejuna, a free version of the play Fuenteovejuna by Lope de Vega, the result of the Llanera Dance and Theater of the Middle Ages and Renaissance courses, of the Department of Performing Arts of the Antonio Nariño University at 2022-2. The analysis of this artistic-pedagogical experience was made from the systematization of the experiences of the creative process of the play. Which allowed us to recognize the fundamental strategies of the creation process; the work with the texts in its adaptation to the Orinoquia context and how to link the scenic action with the joropo, in the way that the verse will be transformed to images that were show in the stage, these were built each scene, then we reflect about the importance of scenic and pedagogical decisions for the understanding of the classics text in our context.